If and , then verify that:

(i) (A’)’ = A


(ii) (AB)’ = B’A’


(iii) (kA)’ = (kA’).


We are given with matrices A and B, such that



(i). We need to verify that, (A’)’ = A.


Take L.H.S: (A’)’


In linear algebra, the transpose of a matrix is an operator which flips a matrix over its diagonal, that is it switches the row and column indices of the matrix by producing another matrix denoted as AT or A’.


So, in transpose of a matrix,


Rows of matrix becomes columns of the same matrix.


So,


If ,


(0, -1, 2) and (4, 3, -4) are 1st and 2nd rows respectively, will become 1st and 2nd columns respectively.


Then


Also, if ,


Similarly, (0, 4), (-1, 3) and (2, -4) are 1st, 2nd and 3rd rows respectively, will become 1st, 2nd and 3rd columns respectively.


Then


Note, that


Thus, verified that (A’)’ = A.


(ii). We need to verify that, (AB)’ = B’A’.


Take L.H.S: (AB)’


Compute AB.



Order of A = 2 × 3


Order of B = 3 × 2


Then, order of AB = 2 × 2


Multiplying 1st row of matrix A by matching members of 1st column of matrix B, then sum them up.


(0, -1, 2)(4, 1, 2) = (0 × 4) + (-1 × 1) + (2 × 2)


(0, -1, 2)(4, 1, 2) = 0 – 1 + 4


(0, -1, 2)(4, 1, 2) = 3



Similarly, repeat the process to find the other elements.






Transpose of AB is (AB)’.


(3, 9) and (11, -15) are 1st and 2nd rows respectively, will become 1st and 2nd columns respectively.



Take R.H.S: B’A’


If ,


(4, 0), (1, 3) and (2, 6) are 1st, 2nd and 3rd rows of matrix B respectively, will become 1st, 2nd and 3rd columns respectively.



Also, if ,


(0, -1, 2) and (4, 3, -4) are 1st and 2nd rows respectively, will become 1st and 2nd columns respectively.



Multiply B’ by A’.



Order of B’ = 2 × 3


Order of A’ = 3 × 2


Then, order of B’A’ = 2 × 2


Multiply 1st row of matrix B’ by matching members of 1st column of matrix A’, then sum them up.


(4, 1, 2)(0, -1, 2) = (4 × 0) + (1 × -1) + (2 × 2)


(4, 1, 2)(0, -1, 2) = 0 – 1 + 4


(4, 1, 2)(0, -1, 2) = 3



Similarly, repeat the same steps to find out other elements.






Since, L.H.S = R.H.S.


Thus, (AB)’ = B’A’.


(iii). We need to verify that, (kA)’ = kA’.


Take L.H.S: (kA)’


We know that,



Multiply k on both sides, (k is a scalar quantity)





Now, to find transpose of kA,


(0, -k, 2k) and (4k, 3k, -4k) are 1st and 2nd rows of matrix kA respectively, will become 1st and 2nd columns respectively.



Take R.H.S: kA’


If


Then, for transpose of A,


(0, -1, 2) and (4, 3, -4) are 1st and 2nd rows of matrix A respectively, will become 1st and 2nd columns respectively.



Multiply k on both sides,





Note that, L.H.S = R.H.S.


Thus, (kA)’ = kA’.


27
1